Investigating the Effects of Consumer Innovativeness, Service Quality and Service Switching Costs on Service Loyalty in the Mobile Phone Service Context - Farzana Quoquab; Nor Liza Abdullah; Jihad Mohammad (Gadjah Mada International Journal of Business, 2016)
The objective of this study is to examine the effects of consumer innovativeness, service quality, service switching costs and service satisfaction on service loyalty among mobile phone service users. A cross sectional survey was employed which yielded 535 responses. Structural equation modelling using the AMOS version 2.0 was utilized to test study the hypotheses. Test results reveal that service satisfaction, service switching costs and service quality are the three antecedents that directly influence service loyalty. However, consumer innovativeness does not have any direct effect on service loyalty. Moreover, service satisfaction is found to be a partial mediator between ‘service quality’ and ‘service loyalty’. Findings from this study will develop insights to enable policy-makers, managers and marketers to better strategize and effectively implement loyalty programs and prevent their customers from switching. This will enhance value creation for both their users and for the industry.